Central Bank Autonomy, and Inflation and Output Performance in the Baltic States, Russia, and Other Countries of the Former Soviet Union, 1995-1997 - Lybek, Tonny (Washington, D.C. : International Monetary Fund, 1999)
A higher degree of de jure autonomy and accountability of the central banks of the Baltic states, Russia, and other countries of the former Soviet Union appears to be positively correlated with lower average inflation. There also seems to be some positive correlation between greater central bank autonomy and higher average real growth, after the initial period of reforms. Central banks with a higher degree of autonomy and accountability have apparently also reformed their operations more aggressively.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet